(untitled) (Research, Society and Development, 2021)
The consumption of inappropriate medications can be important in the occurrence of adverse events and cause harm to patients’ health. It is perceived that internal and external factors, physical and chemical, have the ability to influence the stability of the constituents and can change the nature of clinical outcomes through the use of these drugs. This work aims to survey the literature on changes in the constitution of drugs over the period of validity. This is a literature review where searches were performed for scientific articles in SciELO, LILACS and MEDLINE electronic databases with keywords in agreement with the DECs. The shelf life of medicines is determined through technical evaluations and compliance with health regulations where it is ensured that the drug is suitable for human consumption. After this period or disrespecting these guidelines, it is possible that changes occur in their constitutions that can cause intoxication or lead to intoxication such as NET and Syndrome and Steven Jhonson. The consumption of medications in improper conditions, or expired, has the capacity to increase health risks and can promote sequelae and lethal outcomes. Therefore, measures and surveillance are needed to control the quality, validity, storage and consumption conditions of medicines.